Die Nutzung von Geninformationen für eine personalisierte Pharmakotherapie: Stand, Zukunftspotenziale und wirtschaftliche Implikationen - Sohn, Stefan; Dornstauder, Philipp; Schöffski, Oliver (PharmacoEconomics German Research Articles, 2010)
<div class="AbstractSection" id="ASec1" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Objective <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> In pharmacotherapy „personalised medicine“ based on genetic information has developed in recent years. To assess its implications a review was conducted on its current status, its prospective potential and its impact on health expenditures. <div class="AbstractSection" id="ASec2" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Study design <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> A systematic literature review was conducted to assess personalised/individualised medicine using genetic information in pharmacotherapy. <div class="AbstractSection" id="ASec3" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Results <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Personalised medicine has the potential to optimise medical treatments. The first active agents with a mandatory DNA test are already available. It is predicted that the focus of pharmacogenetics in the future will concentrate on cancer, palliative medicine and psychiatry. Although the present influence on practice is assessed as low, it is assumed that the DNA test will be mandatory in the mid to long-term for a large proportion of cancer therapies. Genetic information may influence the efficacy of approximately 50% of pharmaceuticals in the market. Due to the variety of economic consequences with different effects and still weak evidence no definite forecasts can be given about cost trends. <div class="AbstractSection" id="ASec4" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; color: rgb(51, 51, 51);"> <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Conclusions <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Pharmacogenetics and pharmacogenomics will have a clear impact on pharmacotherapy in the forthcoming years. For a valid estimation of the economic impacts more health economic studies in this context are needed.
WiSo-Import:2015-03-26:1415
Keywords: Forschungsbericht 2010; Innovation